The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1046/j.1432-1327.1998.2550638.x
|View full text |Cite
|
Sign up to set email alerts
|

The third serine proteinase with chymotrypsin specificity isolated from Atlantic cod (Gadus morhua) is a type‐II elastase

Abstract: Preparations of chymotrypsin from Atlantic cod are heterogeneous and previously gave rise to two active peaks when subjected to pH-gradient chromatography. Extension of the pH-gradient resolved a third protein peak with benzoyltyrosine ethylester hydrolytic activity. The first two peaks have been characterized as chymotrypsin variants and designated A and B, whereas the identity of the third peak was not clear. Analysis of this protein by Edman sequencing and mass spectrometry has now confirmed a high degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…When the chymostatin-specific substrate S(Ala) 2 Pro-PhepNA was used, only chymostatin inhibited the proteolysis by D. magna gut homogenate. Another difference found was that elastatinal, which is a specific inhibitor of mammalian elastase, inhibited hydrolysis of the chymotrypsin substrate S(Ala) 2 ProPhepNA in D. magna gut homogenates; a similar finding of a chymotrypsin with characteristics of elastase was recently reported for Atlantic cod (Asgeirsson et al, 1998). Hence, D. magna contains digestive chymotrypsins that differ from vertebrate chymotrypsins in both their sensitivity to inhibitors and their specificity for substrates.…”
Section: Discussionsupporting
confidence: 61%
“…When the chymostatin-specific substrate S(Ala) 2 Pro-PhepNA was used, only chymostatin inhibited the proteolysis by D. magna gut homogenate. Another difference found was that elastatinal, which is a specific inhibitor of mammalian elastase, inhibited hydrolysis of the chymotrypsin substrate S(Ala) 2 ProPhepNA in D. magna gut homogenates; a similar finding of a chymotrypsin with characteristics of elastase was recently reported for Atlantic cod (Asgeirsson et al, 1998). Hence, D. magna contains digestive chymotrypsins that differ from vertebrate chymotrypsins in both their sensitivity to inhibitors and their specificity for substrates.…”
Section: Discussionsupporting
confidence: 61%
“…However, Shotton (1970) reported that elastase can digest a wide variety of other proteins in addition to native elastin. Gastric elastase enzymes have been recovered from marine and fresh water fish species such as carp (Cohen and Gertler, 1981), catfish (Clark, et al, 1985), and Atlantic cod (Asgeirsson and Bjarnason, 1993;Asgeirsson, et al, 1998;Gildberg and Overbo, 1990;Raa and Walther, 1989). Apart from the collagenases distributed in digestive tract, they were also found in fish muscle tissues including skeletal muscle of mackerel, Scomber japonicus, Japanese flounder, Paralichthys olivaceus, rainbow trout and common carp (Sriket, 2014).…”
Section: Collagenases and Elastasesmentioning
confidence: 99%